« Qui sème le vent récolte la tapette ». L’éclosion du militantisme homosexuel en région dans les années 1970 - Mathias Quéré (Les Cahiers de Framespa)
The French gay liberation movement grew throughout the 1970s, following the examples of other issue-specific movements. The first Group for Gay Liberation (Groupe de Libération Homosexuel or GLH) was born in the spring of 1974. Only a few months later, more than twenty similar groups had emerged all over France. For the first in the history of the French gay liberation movement, this new form of militancy spread nationwide and was not solely a Parisian affair. Beyond the quest for visibility, the activists strove to build a true political movement, in tune with the time and in close partnership with the feminist movement. This article will explore not just the story of this militant commitment but also that of a genuine claim of identity that sought to deeply upset the norms by using the motto « the private is political ».